2012
DOI: 10.1590/s0100-06832012000200006
|View full text |Cite
|
Sign up to set email alerts
|

Atributos físicos nos tempos de adoção de manejos em Latossolo cultivado com soja

Abstract: Atributos Físicos nos tempos de Adoção de mAnejos em LAtossoLo...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Thus, it is important to consider all factors involved in the process of soil compaction. Rosseti et al (2012) reported that the desirable level of soil moisture content for optimum soil compaction for a soil with 340 g kg -1 of clay is from 0.13 to 0.19 kg kg -1 . Soil moisture content in this study was >0.22 kg kg -1 , for a matric potential of <10 MPa.…”
Section: Soil Physical Propertiesmentioning
confidence: 99%
“…Thus, it is important to consider all factors involved in the process of soil compaction. Rosseti et al (2012) reported that the desirable level of soil moisture content for optimum soil compaction for a soil with 340 g kg -1 of clay is from 0.13 to 0.19 kg kg -1 . Soil moisture content in this study was >0.22 kg kg -1 , for a matric potential of <10 MPa.…”
Section: Soil Physical Propertiesmentioning
confidence: 99%
“…Soils with a higher friability better resist compression from surface pressures [43], but above this limit (in the plastic range) they offer favorable conditions for compaction [44]. Thus, it was observed that the mechanized harvesting sugarcane area presented a range of friability with water content between 0.20-0.34 kg kg −1 , whereas the burned harvest soil showed a friability ranging from 0.19-0.31 kg kg −1 , and the forest area, between 0.19-0.32 kg kg −1 (Figure 2).…”
Section: Comparison Of Models Between Layers Within the Managementmentioning
confidence: 99%